Perancangan Aplikasi Monitoring Pemberian Pakan Otomatis Berbasis Mobile Menggunakan Metode Mobile-D - Dede Brahma Arianto; Risya Sholehatun Nisa; Ahmad Sanusi; Muhamad Farhan Qolbi (Jurnal ELIT, 2026)
Feed plays a fundamental role in aquaculture activities because it is directly related to the productivity and sustainability of cultivated organisms. Manual feeding often causes various problems, including inaccurate dosages, irregular feeding times, and limitations in the monitoring process. This research focuses on the design and development of an automatic feeding system that can be controlled and monitored via mobile devices by applying the Mobile-D method as a software development approach. The system developed combines Internet of Things technology with a mobile application to support feeding schedule management, device condition monitoring, and real-time data management. The research stages include needs analysis, system and interface design, application implementation, and functionality testing. The development results show that the system is able to operate according to its designed functions, providing ease in feeding management, and increasing the efficiency and accuracy of the maintenance process. Therefore, this system can be an alternative solution in supporting mobile technology-based aquaculture management.